Perceived stress and humanistic care ability among Chinese healthcare workers: The chain mediating role of social support and life satisfaction - Wang, Zonghua; Xie, Langlang; Liang, Zeping; Fan, Jiangshan; Fan, Liqi; Deng, Jing; Xu, Xia (Frontiers in Psychology, 2022)
Previous studies have indicated high perceived stress and its relationship with life satisfaction among healthcare workers. However, most of the existing studies have focused on the investigation and evaluation of the humanistic care abilities among nurses, but few studies revealed the levels of humanistic care ability among other healthcare workers including doctors and technicians. The study aimed to investigate the perceived stress and the humanistic care abilities among Chinese healthcare workers. In addition, we further examined the mediating and moderating effects of social support and life satisfaction. A convenience sample of 955 health professionals from 29 hospitals in China were recruited to fill out the questionnaires of perceived stress, humanistic care ability, social support and life satisfaction. The correlation and multivariate logistic regression analysis were carried out by SPSS 24.0. The Hayes SPSS macro program process (version 2.16.3) was used to analyze the significance of mediating and moderating model. The findings indicated that humanistic care ability negatively associated with perceived stress and positively correlated with social support and life satisfaction. The effect of the path “perceived stress→social support→humanistic care ability” was -0.071, and the path “perceived stress→life satisfaction→social support→humanistic care ability” was -0.129. The current study contributed to a better understanding of the humanistic care abilities and influential factors in Chinese healthcare workers. Thus it may suggest studies on interventions to interventions to alleviate or eliminate the negative impact of perceived stress and improve the humanistic care abilities.